2021
DOI: 10.1186/s40794-021-00154-2
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis infections among hospital patients, Sarawak, Malaysia

Abstract: Background Leptospirosis diagnoses have increased in Sarawak, Malaysia in recent years. Methods To better understand the burden of disease and associated risk factors, we evaluated 147 patients presenting with clinical leptospirosis to local hospitals in Sarawak, Malaysia for the presence of Leptospira and associated antibodies. Sera and urine specimens collected during the acute illness phase were assessed via a commercially available rapid diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
2
3
0
Order By: Relevance
“…When test performance was categorized by day after the onset of symptoms, the results were similar to overall performance. The sensitivity of RPA-CRISPR/Cas12a FBDA peaked on day < 4 after the onset of fever and decreased with time whereas sensitivity of Leptospira IgM RDTs increased on day 4–6 and declined on day > 6, similar to previous findings [ 13 , 14 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When test performance was categorized by day after the onset of symptoms, the results were similar to overall performance. The sensitivity of RPA-CRISPR/Cas12a FBDA peaked on day < 4 after the onset of fever and decreased with time whereas sensitivity of Leptospira IgM RDTs increased on day 4–6 and declined on day > 6, similar to previous findings [ 13 , 14 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…When test performance was categorized by day after the onset of symptoms, the results were similar to overall performance. The sensitivity of RPA-CRISPR/Cas12a FBDA peaked on day < 4 after the onset of fever and decreased with time whereas sensitivity of Leptospira IgM RDTs increased on day 4-6 and declined on day > 6, similar to previous findings [13,14,22]. Leptospires are normally present in the blood during the first week and are eliminated by the host-immunity while IgM and IgG antibody levels begin to rise and reach their peak during the second week of illness [11].…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, there have been increasing numbers of leptospirosis infection cases in Malaysia [ 18 , 19 , 20 ]. A case report showed that a real-time PCR assay was successfully used in a postmortem diagnosis of a woman whose death was caused by L. interrogans [ 21 ]. One study reported positively detected Leptospira cases and related risk factors in Sarawak, Malaysia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few people also experienced severe leptospirosis after swimming in a waterfall [ 92 ] and kayaking in a river [ 93 ]. In Sarawak, the weekly washing of clothes in local rivers was associated with leptospirosis among hospital patients [ 73 ]. Among wet market workers in two locations were 33.6% [ 76 ] and 46.3% [ 78 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…congkakensis[69]. In humans, L. weilii, L. kirschneri, L. wolffii, and L. interrogans[71][72][73][74] were detected.New serovars are also continuously being discovered. A serovar known as Malaysia was isolated from the soil samples of Johor state in 2009[75].…”
mentioning
confidence: 97%